(untitled) (Eurasian Journal of Ecology, 2016)
The regularities of chemism formation in salt-dome areas of Pricaspian lowland have been evaluated. The results of hydro chemical and toxicological screening of the spring on Inder lake of Pricaspian lowland have been submitted. The content of kathions and anions, heavy metals, oil products in hydro chemical samples of spring water have been characterized in comparison with the sanitary norms and requirements to the water quality.